2007
DOI: 10.1016/j.jtcvs.2007.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of head-down tilt on intrapulmonary shunt fraction and oxygenation during one-lung ventilation in the lateral decubitus position

Abstract: Head-down tilt during one-lung ventilation in the lateral decubitus position caused a significant increase in shunt and a decrease in percent change of arterial oxygen tension, without causing dangerous hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Many studies have shown that a decrease in flow leads to a preferential increase in the perfusion of the normoxic (ventilated) lung, and the magnitude of HPV is flowdependent in the hypoxic lung region [16,17]. In our study, the values of CO stayed in a similar range in the two groups throughout the entire experiment, which meant that intravenous HOS had no significant influence on CO during OLV.…”
Section: Discussionsupporting
confidence: 46%
“…Many studies have shown that a decrease in flow leads to a preferential increase in the perfusion of the normoxic (ventilated) lung, and the magnitude of HPV is flowdependent in the hypoxic lung region [16,17]. In our study, the values of CO stayed in a similar range in the two groups throughout the entire experiment, which meant that intravenous HOS had no significant influence on CO during OLV.…”
Section: Discussionsupporting
confidence: 46%
“…However, Mitlyng et al had identified a similar 25% shorter RBC lifespan in patients with arthritis limiting mobility and with chronic anemia 75 . Therefore, low-grade hemolysis may be the mechanism explaining the high prevalence of anemia in patients who remain bedridden for prolonged durations [76][77][78][79][80] . In these patients, different approaches may be needed to address increased hemolysis with bed rest.…”
Section: Discussionmentioning
confidence: 99%
“…Should these parameters not be met, oxygen delivery to the cells will be inadequate, leading to anaerobic metabolism and potential multi-organ failure. One of the reasons for clinical ventilation/perfusion mismatch can be pulmonary pathology, leading to so called shunt [ 1 3 ], another is—patient positioning on the operating table [ 4 , 5 ]. While young and healthy subjects can cope this scenario due to the efficiency of their physiological reflexes, in medicine, many surgical procedures involve elderly and critically ill patients with significant health impairments [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%